Is urban agriculture sustaining the urban poor? a study of grandmother headed households (GHHs) in Bulawayo, Zimbabwe - Hungwe, Chipo (Taylor & Francis, 2022)
In this study of urban agriculture in Bulawayo, I examine the extent to which the activity sustains the poor and reduces social exclusion in grandmother-headed households. A qualitative case study design was employed to study the lives of 19 older women. Findings indicate that urban agriculture does not assist in reducing food insecurity and social exclusion among the research participants because of several factors. Challenges in acquiring farming land, medical conditions, and the strenuous and less integrated nature of the urban agriculture practice affect the extent to which urban agriculture secures families from hunger. Social assistance is needed for members of grandmother-headed households.